How Peer Support Enables a More Sustainable Professional Medical Role: A Qualitative Study - Horne, Ingrid Marie Taxt; Veggeland, Frode; Bååthe, Fredrik; Isaksson Rø, Karin (Professions and professionalism, 2025)
Peer support services have been established in several professions to help individuals cope with challenging work and life situations. Using the medical profession as an example, we have qualitatively studied physicians’ experiences of peer support. We conducted interviews with 12 physicians shortly after they had attended peer support and 12 months later. We analysed the interviews using systematic text condensation. We then reanalysed each pair of interviews (baseline and follow-up) using Schein’s model to further deepen the analytical insights. The results show that the professional medical role can evolve. Peer support helped the individual physician to become aware of, acknowledge and adjust to how unwritten rules within the medical culture had formed a non-sustainable professional role. Peer support can facilitate changes at and outside work, as well as foster a willingness to seek treatment for self-care.